Tipologi Koperasi Umum dan Syariah - Amir Sup, Devid Frastiawan; Lahuri, Setiawan; Kamaluddin, Imam; Ghozali, Mohammad; Hidayat, Iman Nur (Al-Intaj : Jurnal Ekonomi dan Perbankan Syariah, 2022)
This study aims to typify cooperatives in Ponorogo, East Java, Indonesia. The data used as the object of the typology are 842 cooperative data. This study used a quantitative descriptive methodology with a typology approach. Data were collected using the documentation method and typologically using the descriptive analysis method. The results obtained are that there are 430 cooperatives that have been certified by NIK certtified and 412 cooperatives that have not been certified by NIK certified. Cooperatives in Ponorogo, East Java, Indonesia can be typified into 4 (four): (1) Based on level (primary cooperative, secondary cooperative, and cooperative center); (2) Based on activity (KSP, KSU, KBPR, producer cooperative, consumer cooperative, service cooperative, and handicraft industry cooperative); (3) Based on member (KPN-KPRI, employee cooperative, student cooperative, KUD, women's cooperative, and market cooperative); (4) Sharia entities (sharia cooperative, KJKS-KSPPS, Kopontren, and BMT).